Complications of temperature-controlled radiofrequency volumetric tissue reduction for sleep-disordered breathing - Stuck, Boris; Starzak, Katrin; Verse, Thomas; Hörmann, Karl; Maurer, Joachim T. (Acta oto-laryngologica, 2003)
Objective-Temperature-controlled radiofrequency volumetric tissue reduction (RFVTR) is a minimally invasive technique used in the treatment of the tongue base, soft palate and turbinates. Complications seem to be rare, but the scope of previous studies was often limited by the small number of patients included. The aim of this study was to evaluate postoperative complications in a large series of patients. Material and Methods-In this retrospective study, temperature-controlled radiofrequency procedures (Somnoplasty®) performed between May 1998 and March 2002 were considered. The charts of the patients were analyzed with regard to intra- or postoperative complications. Results-In total, 322 patients received 497 treatment sessions; 239 of these treatments were isolated and the remaining 258 were combined procedures. Mean follow-up was 122.8±145.5 days. Concerning radiofrequency surgery, nine postoperative complications were observed (2.0%) as follows: ulcerations of the tongue base or soft palate; dysphagia necessitating hospital admission; temporary palsy of the hypoglossal nerve; and an abscess of the base of the tongue. Conclusions-Complications occurring after RFVTR are infrequent and mostly mild. Overall, temperature-controlled RFVTR is a safe procedure when used both in isolation and as part of a combined approach.